Peranan Komunikasi Antarpersona Orang Tua terhadap Kemampuan Penyesuaian Sosial Siswa di Sekolah - Kahfi, Agus Sofyandi (Mediator, 2006)
Many factors contribute student’s failure in social adaptation. Parents busy schedule, the lack of quality in communication and interaction, also interpersonal communication failure are exemplars of such factors. In order to improve student’s ability to successfully adapt themselves in social spaces, a strong interpersonal communication was needed. DeVito outlined some characteristics of interpersonal communication: openness, empathy, supportiveness, positiveness, and equality. By applying the principles of interpersonal communication, parents could help their children socialization in school. In turn, it could help their children to gain better academic achievements.